Mercuriales - Ferraro, James 1986- (Shellac, 2015)
"In a Parisian suburb of Bagnolet two receptionists who work in the lobby of the titular high-rise drift from one enigmatic situation to the next going to the pool, visiting a maze-like sex club and hunting for new employment." [imdb.com]
Original: Frankreich 2014
Keywords: Film; DVD-Video